The role of Baitul Maal in improving community welfare through business capital assistance - Ulfa, Nadia; Harahap, Isnaini (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This research aims to examine the role of Baitul Maal in enhancing community welfare through business capital assistance, focusing on MSMEs in Aceh Singkil. Employing a descriptive qualitative research design, the study used interviews to gather relevant stakeholder insights. The findings indicate that Baitul Maal in Aceh Singkil has significantly improved community welfare by providing essential business capital assistance to MSMEs. The study identifies various disbursement processes and specific requirements that potential beneficiaries, referred to as mustahik, must meet to qualify for assistance. The findings can guide policymakers in creating a supportive environment for MSMEs, ultimately fostering economic growth and community welfare. By enhancing the operational framework of Baitul Maal, this research contributes to the broader discourse on effective community empowerment strategies through Islamic financial institutions. Public interest statements The insights gained from this research have several practical implications. First, they highlight the importance of streamlining the disbursement processes to ensure timely and efficient access to capital for MSMEs. Second, the identification of specific requirements for mustahik can inform Baitul Maal and other stakeholders in developing targeted outreach and support programs to serve eligible beneficiaries better. Article Info: Received 7/9/2024 | Revised: 9/18/2024 | Accepted: 9/23/2024 | Online First 9/30/2024